A Legacy Unrivaled : The Story of John Gagliardi - Bostrom, Boz (Book collections on Project MUSE., 2016)
"John Gagliardi, who served as the head football coach at Saint John's University from 1953 to 2012, won more college football games than any coach at any level of collegiate ball. His innovative and unconventional approach to coaching--including not allowing tackling during practices--helped the team win nearly five hundred games and four national championships. A Legacy Unrivaled explores the man, his football philosophy, his life lessons, his sense of humor, and his connections to others through a very personal journey by author and former player Boz Bostrom"--